2006
DOI: 10.1289/ehp.8404
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Toxicology: Population-Level Effects of Chronic Contaminant Exposure on the Marsh Frogs ( Rana ridibunda ) of Azerbaijan

Abstract: We used molecular methods and population genetic analyses to study the effects of chronic contaminant exposure in marsh frogs from Sumgayit, Azerbaijan. Marsh frogs inhabiting wetlands in Sumgayit are exposed to complex mixtures of chemical contaminants, including petroleum products, pesticides, heavy metals, and many other industrial chemicals. Previous results documented elevated estimates of genetic damage in marsh frogs from the two most heavily contaminated sites. Based on mitochondrial DNA (mtDNA) contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 47 publications
(78 reference statements)
0
49
1
Order By: Relevance
“…A number of studies observed genetic responses in populations exposed to chemical pollution (e.g. (Theodorakis and Shugart 1997;Baker et al 2001;Matson 2006;Wirgin et al 2011). Similarly to more traditional effect end-points, trans-generational and evolutionary impacts can result in altered population dynamics and possibly ecosystem structure and functioning.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies observed genetic responses in populations exposed to chemical pollution (e.g. (Theodorakis and Shugart 1997;Baker et al 2001;Matson 2006;Wirgin et al 2011). Similarly to more traditional effect end-points, trans-generational and evolutionary impacts can result in altered population dynamics and possibly ecosystem structure and functioning.…”
Section: Introductionmentioning
confidence: 99%
“…A central goal of evolutionary toxicology is to examine both the direct and indirect effects of toxicant and contaminant exposure on the genetic structure of natural populations (Bickham et al, 2000;Matson et al, 2006;Theodorakis et al, 2001). A chief advantage of evolutionary toxicology over traditional ecotoxicological studies is that the utilisation of molecular and population genetics methodologies means these studies are based on fundamental evolutionary concepts.…”
Section: Evolutionary Toxicologymentioning
confidence: 99%
“…contaminant-induced increases in mutation rates, resulting in changes in genetic frequencies in impacted populations (e.g. Matson et al, 2006;Theodorakis et al, 2001); 2. contaminant-induced selection at loci affecting survival success, resulting in changes in genetic frequencies in the population (e.g. Cohen, 2002;; 3. alterations to patterns of genetic distribution and migration, leading to demographic shifts (e.g.…”
Section: Evolutionary Toxicologymentioning
confidence: 99%
See 2 more Smart Citations